THE EFFECTS OF VOCABULARY MASTERY AND LOGICAL REASONING TOWARDS STUDENT’S LISTENING SKILL - Nina Dwiastuty (Deiksis, 2014)
This research is aimed as follows : To get emperical data and analyze the effects of vocabulary mastery and logical reasoning towards student’s listening skill at Senior Private School in South Jakarta. This research is done by Kolmogorov-Smirnov method, ANOVA Table, Proportional Correct for testing the item difficulties, by biserial coefficient, and by Kuder Richarsson testing. The research was held at Private Senior High School in South Jakarta. Data collective done by giving test for listening skill (yes/no or true false / 37 items), test for vocabulary mastery (multiplechoice/ 20 items), and test for logical reasoning (multiplechoice/20 items) given to class at SMA Kharismawita, SMA Bunda Kandung and SMA 28 Oktober.The result of study identifies; 1. there is an effect of Vocabulary Mastery towards Student’s Listening skill. 2. There is an effect of logical reasoning towards student’s listening skill. And 3.There are effect of vocabulary mastery and logical reasoning towards student’s listening skill.Keywords: Vocabulary Mastery, Logical reasoning, Listening Skill